2013
DOI: 10.1111/cen.12148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on thyroid functions in Indian children

Abstract: Serum FT3 and TSH were positively while FT4 was negatively associated with BMI in apparently healthy euthyroid children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
8
25
1
3
Order By: Relevance
“…In different studies, obese subjetcs had high or normal TT3 and TT4 levels respect to control groups, also TT4 and fT4 levels were inversely coorelated with body weight (6,15,(19)(20)(21)(22)(23)(24), but we didnt't find any difference in fT3, fT4, TT4 between obese and control group.…”
Section: Discussioncontrasting
confidence: 63%
“…In different studies, obese subjetcs had high or normal TT3 and TT4 levels respect to control groups, also TT4 and fT4 levels were inversely coorelated with body weight (6,15,(19)(20)(21)(22)(23)(24), but we didnt't find any difference in fT3, fT4, TT4 between obese and control group.…”
Section: Discussioncontrasting
confidence: 63%
“…In a cohort study of 88 children and adolescents with SCH, 28.4% were found to be overweight or obese, although this high prevalence may be due to selection bias [126]. However, a large community-based study has also shown a significantly higher prevalence of SCH in obese children as compared to non-obese children (9 vs. 6.5%) [148]. In another large cohort study of 22,747 children and adolescents with type 1 diabetes, 1,638 (7.2%) were found to have SCH.…”
Section: Sch In Childhoodmentioning
confidence: 99%
“…Nevertheless, modest alterations in thyroid function are more common among obese compared to lean children, including elevated serum concentrations of thyroid-stimulating hormone (TSH) combined with normal serum concentrations of free thyroxine (fT 4 )-often termed subclinical hypothyroidism (SH) (4,5,6,7,8,9). SH is a diagnosis of exclusion which does not cause any clinical symptoms of hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, central fat accumulation in obese children is associated with a range of metabolic comorbidities and development of cardiovascular complications (15). Although there exist various studies evaluating thyroid status in children with obesity, most studies have focused on body mass index (BMI) standard deviation score (SDS) as the anthropometric measure to describe the degree of obesity (5,6,7,14). Few studies have investigated associations with other anthropometric measures such as waist circumference (WC) (16,17) and waist-hip ratio (17).…”
Section: Introductionmentioning
confidence: 99%